TUNTUTAN PIDANA DALAM PENYELESAIAN SENGKETA PERJANJIAN DI INDONESIA - ALLAN MUSTAFA UMAMI; HERA ALVINA SATRIAWAN (GANEC SWARA, 2024)
Agreement disputes in Indonesia occur due to non-fulfillment of the rights of one party in the agreement by the other party. The agreement is made to serve as strong evidence if a dispute arises in the future. An agreement is a material law that applies to the parties who make it in accordance with the principle of pacta sunt servanda in Article 1338 of the Civil Code (KUHPer). The nature of this material law regulates the parties, but formal law is needed which aims to enforce this material law, which is also known as procedural law. In the event that an agreement is not fulfilled and a dispute arises, it can be caused by a breach of contract, an unlawful act, a defect in the will known in the Civil Code which is resolved through formal civil law mechanisms. It is possible that other legal remedies could be taken by the injured party, namely through a formal criminal law approach. The criminal settlement approach is used with the intention that the party who is charged or sued immediately completes his obligations. Of course, criminal efforts cannot immediately interfere in civil cases without there being evidence that there is a criminal element or a legal basis for the dispute to be directed to criminal prosecution. The formulation of the problem in this research is what is the law of criminal prosecution in resolving contractual disputes in Indonesia? The purpose of this research is to determine the law of criminal prosecution in resolving contractual disputes in Indonesia. The research method used in this research is normative legal research. The results of the research state that criminal charges to resolve agreement disputes are very possible provided that one of the parties has been proven to have committed a criminal act in the pre-agreement, agreement and post-agreement stages and with the proven criminal act being the basis for the aggrieved party to add to the claim for an unlawful act. regulated in Article 1365 of the Civil Code